2013
DOI: 10.1055/s-0033-1356548
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension Complicating Interstitial Lung Disease and COPD

Abstract: Pulmonary hypertension (PH) may complicate parenchymal lung disease, specifically interstitial lung diseases and chronic obstructive pulmonary disease, and uniformly increases the mortality risk. The epidemiology and degree of PH is variable and unique to the underlying lung disease. The clinician should exercise a high index of suspicion for PH complicating parenchymal lung disease especially given the nonspecific symptomatology and the limitations of echocardiography in this patient population. In general, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 221 publications
(380 reference statements)
0
3
0
Order By: Relevance
“…The EQ-5D health questionnaire was applied to assess the QoL for COPD patients [ 7 , 9 ]. The self-classifier consists of five dimensions (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression), each with three levels of response (level 1 = no problems, level 2 = some problems, or level 3 = inability or extreme problems).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EQ-5D health questionnaire was applied to assess the QoL for COPD patients [ 7 , 9 ]. The self-classifier consists of five dimensions (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression), each with three levels of response (level 1 = no problems, level 2 = some problems, or level 3 = inability or extreme problems).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies found that proper health interventions could both improve the quality of life (QoL) and reduce the medical costs of COPD patients [ 6 - 8 ]. QoL is likely an important predictor for subsequent COPD exacerbation, hospitalization and mortality, and is related to the severity of COPD, which all are measures associated with a high healthcare expenditure [ 9 - 12 ]. Also, QoL is strongly associated with investment beliefs and their behaviors including healthcare seeking [ 13 - 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…PH associated with lung disease has the worst prognosis of all types of PH [2]. The prevalence of PH in both chronic lung diseases depends on the severity of the disease and the definition and methodologies used in the studies [3, 4]. Most of the available data regarding PH-lung disease comes from patients undergoing evaluation for lung transplantation (LTx).…”
Section: Introductionmentioning
confidence: 99%